(untitled) (Journal of the College of Basic Education, 2024)
The research examined the mechanisms for selecting suitable sites for water harvesting, due to their importance to the region in which the Wadi Shahban basin is located within the borders of the Jazira desert, which is characterized by drought and fluctuations in the amount of rainfall falling from one season to another. The American Soil Conservation Hypothesis (SCS-CN) was used to estimate the volume of surface runoff through a set of indicators represented by finding the relationship ratios between land cover types and hydrological soil types to measure the nature of the valley surface for permeability and infiltration based on remote sensing techniques and geographic information systems (GIS). It was found that the values of (CN), which ranged between (79-91), had adequate surface runoff, and then the depth of surface runoff (Q) for the Wadi al-Wadi basin was estimated, as it ranged between (37.3-113.88), leading to the estimation of the volume of annual surface runoff (QV). ) whose lowest value was (0.261 m3) and highest (48.057 m3).